2004
DOI: 10.1111/j.1364-3703.2004.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding cell development by cyst and root‐knot nematodes involves a similar early, local and transient activation of a specific auxin‐inducible promoter element

Abstract: SUMMARY To study the role of the phytohormone auxin in nematode feeding cell induction and early development, the transcriptional regulation of the artificial auxin-responsive promoter element DR5 was monitored in Arabidopsis thaliana roots infected with the cyst nematode Heterodera schachtii or the root-knot nematode Meloidogyne incognita. For both nematode species, a specific and strong activation of DR5::gusA was observed inside the initial feeding cells at 18 h post inoculation, pointing to an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 16 publications
6
105
1
1
Order By: Relevance
“…The expression of the efflux transporter PIN1 is downregulated in the initial syncytial cell, preventing the drain of auxin and thus assisting AUX1 in accumulating auxin in these cells (Grunewald et al, 2009). Interestingly, auxin accumulation in young NFS is only transient, and between 2 and 5 d after the initial infection the auxin response shifts to the neighboring cells (Hutangura et al, 1999;Karczmarek et al, 2004;Grunewald et al, 2008). This observation argues again for the involvement of auxin transport and resembles the auxin response that occurs during formation of other plant organs.…”
Section: Nematode Infection Requires Changes In the Host's Auxin Respmentioning
confidence: 89%
See 1 more Smart Citation
“…The expression of the efflux transporter PIN1 is downregulated in the initial syncytial cell, preventing the drain of auxin and thus assisting AUX1 in accumulating auxin in these cells (Grunewald et al, 2009). Interestingly, auxin accumulation in young NFS is only transient, and between 2 and 5 d after the initial infection the auxin response shifts to the neighboring cells (Hutangura et al, 1999;Karczmarek et al, 2004;Grunewald et al, 2008). This observation argues again for the involvement of auxin transport and resembles the auxin response that occurs during formation of other plant organs.…”
Section: Nematode Infection Requires Changes In the Host's Auxin Respmentioning
confidence: 89%
“…Similar to nodule initiation, an enhanced auxin response has been visualized at the infection sites of both cyst and root-knot nematodes, whereas auxin signaling mutants have shown significantly lower nematode infection (Hutangura et al, 1999;Goverse et al, 2000;Karczmarek et al, 2004;Grunewald et al, 2008). This suggests that auxin might trigger the initiation of both giant cells and syncytia and that auxin-dependent programs are needed for NFS establishment.…”
Section: Nematode Infection Requires Changes In the Host's Auxin Respmentioning
confidence: 94%
“…Various lines of evidence also have implicated auxin and cytokinin flux in the RKN-host interaction (Mathesius et al, 1998;Hutangura et al, 1999;Karczmarek et al, 2004;Lohar et al, 2004) as part of the regulation of root architecture. Thus, rather than focus on gene expression in GCs per se, we designed experiments to interrogate genes representative of the broader tomato root transcriptome during compatible and incompatible interactions with RKN.…”
mentioning
confidence: 99%
“…It was shown by Goverse et al (2000) and Karczmarek et al (2004) that auxin plays a crucial role in the development of nematode feeding sites. They suggested that nematodes are able locally to increase auxin concentration, thus in turn enhancing ethylene production.…”
Section: Plant Hormones Affect Expression Of Atcel2 and Kor3mentioning
confidence: 99%
“…glucanases) but also plant hormones or hormone-related compounds (De Meutter et al, 2005). On the other hand, nematodes are able to alter the hormone homeostasis within feeding sites, as shown by Goverse et al (2000) and later by Karczmarek et al (2004). Both strategies may influence expression of essential genes and thereby support the change from healthy root tissue to a feeding site.…”
Section: Introductionmentioning
confidence: 99%